High Blood Flow Into the Femur Indicates Elevated Aerobic Capacity in Synapsids Since the Synapsida-Sauropsida Split - Knaus, Philipp L.; van Heteren, Anneke H.; Lungmus, Jacqueline K.; Sander, P. Martin (Frontiers in Ecology and Evolution, 2021)
Varanids are the only non-avian sauropsids that are known to approach the warm-blooded mammals in stamina. Furthermore, a much higher maximum metabolic rate (MMR) gives endotherms (including birds) higher stamina than crocodiles, turtles, and non-varanid lepidosaurs. This has led researchers to hypothesize that mammalian endothermy evolved as a second step after the acquisition of elevated MMR in non-mammalian therapsids from a plesiomorphic state of low metabolic rates. In recent amniotes, MMR correlates with the index of blood flow into the femur (Qi), which is calculated from femoral length and the cross-sectional area of the nutrient foramen. Thus, Qi may serve as an indicator of MMR range in extinct animals. Using the Qi proxy and phylogenetic eigenvector maps, here we show that elevated MMRs evolved near the base of Synapsida. Non-mammalian synapsids, including caseids, edaphosaurids, sphenacodontids, dicynodonts, gorgonopsids, and non-mammalian cynodonts, show Qi values in the range of recent endotherms and varanids, suggesting that raised MMRs either evolved in synapsids shortly after the Synapsida-Sauropsida split in the Mississippian or that the low MMR of lepidosaurs and turtles is apomorphic, as has been postulated for crocodiles.